FINANCIAL MANAGEMENT ACCOUNTABILITY IN THE PERSPECTIVE OF SHARI’AH ENTERPRISE THEORY - Nadhilah Amaliah Liwan; Memen Suwandi; Lince Bulutoding (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Shari'ah Enterprise Theory (SET) is a theory that explains accountability not only to stakeholders but to wider stakeholders, namely God, humans, and nature. The purpose of this study is to examine financial management accountability in the perspective of Shari`ah Enterprise Theory at the Ministry of Religion of East Luwu Regency. This study uses a phenomenological approach with qualitative methods that rely on data in the form of text and images to understand meaning. The results of the study show that the financial management of the Ministry of Religion of the East Luwu Regency in managing its finances has fulfilled the principles of accountability and good governance which can be seen from the planning process to reporting and accountability carried out based on the provisions and regulations in force. In addition, the Ministry of Religion of East Luwu Regency has instilled spiritual values in managing state finances by being aware of accountability to Allah, humans and nature in accordance with the principles of the shari`ah enterprise theory.